Multiple Ascending Dose Safety, Tolerability, and Pharmacokinetics of KBP-7072, a Novel Third-generation Tetracycline. (4th October 2017) - Yang, Fred; Wang, Yanli; Wang, Ping; Hong, Mei; Benn, Vincent
Abstract: Background: KBP-7072 is a novel aminomethylcycline exhibiting broad-spectrum activity against Gram+ and Gram- multidrug-resistant bacterial isolates and strains. KBP-7072 has previously been studied in a single ascending dose study up to 300 mg in healthy adults. Methods: This was a randomized, single-blind, placebo-controlled, sequential parallel-group, multiple ascending dose study to evaluate the safety, tolerability, and pharmacokinetics (PK) of KBP-7072 in healthy adults. Four cohorts were planned with 8 subjects (6 KBP-7072, 2 placebo) in each cohort to evaluate KBP-7072 100 mg QD, 200 mg QD, 300 mg QD, and 200 mg BID for 10 days. Dose escalation stopped following completion of the 200 mg QD cohort. Safety, tolerability, and PK were evaluated for each cohort. Results: 16 subjects (male: 87.5%; 18–55 years of age) were enrolled including 8 in each of the 2 dose escalation cohorts (100 mg QD and 200 mg QD). After the results of the first two cohorts (100 mg QD and 200 mg QD) were analyzed, it was determined that the therapeutic dose of KBP-7072 was likely to be less than 200 mg/day. All treatment-emergent adverse events (TEAEs) were of mild intensity, resolved without intervention, and most TEAEs were assessed as either unrelated or probably unrelated to treatment. No serious adverse events were reported. Elevated alanine aminotransferase was reported in 4 subjects (all in the 200 mg QD cohort) who were asymptomatic and recovered without intervention. PK data included in the table below suggests that exposure is approximately dose proportional. Conclusion: This study demonstrated that KBP-7072 was safe and generally well-tolerated at doses up to and including 200 mg QD. Disclosures: F. Yang, KBP Biosciences Co., Ltd.: Employee, Salary. Y. Wang, KBP Biosciences USA Inc.: Employee, Salary. P. Wang, KBP Biosciences Co., Ltd.: Employee, Salary. M. Hong, KBP Biosciences: Employee, Salary. V. Benn, KBP Biosciences USA Inc.: Employee, Salary.